Directive Speech Acts in Election Socialization Videos on the General Elections Commission Republic Indonesia Youtube Channel - Vika Fransisca (Pusat Publikasi Nusantara, 2026)
Directive speech is the delivery of something to the speech partner so that the speech partner takes an action in the form of doing something that has been done before, or an action desired by the speaker. The purpose of this study is to identify the types of directive speech acts used in socialization videos on the KPU RI YouTube channel. The research method used is a qualitative descriptive method, with data in the form of directive speech from socialization videos on the KPU RI YouTube channel. Data collection was carried out by the listening method, namely listening to the speech used in communication in the campaign socialization video. Data analysis uses normative techniques, focusing on the analysis of directive speech actions in the video studied. The results of the research from 5 videos that have been analyzed obtained the results of 4 types of directive speech actions used, namely orders, prohibitions, suggestions, and invitations. Directive speech is conveyed using a direct speech communication strategy, aimed at the people of Indonesia, especially generation Z.